TUGAS PANGGILAN GEREJA KOINONIA: KEPEDULIAN ALLAH DAN TANGGUNG JAWAB GEREJA TERHADAP KEMISKINAN - Stimson Hutagalung (Jurnal Koinonia, 2016)
Injustice will bring social problems, especially in terms of economy. This will bringup the poverty and misery in the midst of society. The Church played important rolein overcoming poverty and also become one of the responsibilities of Jesus’followers. Christianity must concern and caring to the poor and suffer and shouldplay an active role in overcoming the problem of poverty due to the accountability inlast judgement. Churches in the world, including Seventh-day Adventist Church,take responsible to reduce poverty problem.